The art of changing the brain : enriching teaching by exploring the biology of learning - Zull, James E. (James Ellwood), 1939- (Stylus Pub., 2002)
"Learning is a vast and complex topic that cannot be easily defined, and biological descriptions of processes in learning are similarly complex - thus, this book generalizes on both counts and will likely feel/sound somewhat inaccurate or incomplete to many readers. Nonetheless, we can enrich our teaching with a better understanding of the biology of the brain"--Author